Analisis Faktor-faktor yang Mempengaruhi Pemilihan Karir Mahasiswa Akuntansi Sebagai Auditor - Ega Erlianti; Juanda Astarani; Djunita Permata Indah (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
Finding out what factors motivate students to become auditors is the driving force behind this research. Tanjungpura University, Pontianak, sixth-semester accounting students were surveyed to gather primary data. One hundred participants were chosen at random for this research. Questionnaires using Likert scales were used to collect data. According to the data, students are more interested in becoming auditors when they are offered financial incentives, a nice work environment, opportunities for professional development, and competitive salaries.